On Chesil Beach a novel - McEwan, Ian (Anchor Books, 2008)
aOn their wedding day, a young couple--Florence, daughter of an Oxford academic and a successful businessman, and Edward, an earnest history student with little experience of women--looks forward to the future while worrying about their upcoming wedding night.